Ekspresi Tutur Pejabat Publik dalam Wacana Percakapan Virtual di Facebook (Public Officials' Speech Expressions in Virtual Conversation Discourse on Facebook) - Erwin Erwin (Indonesian Language Education and Literature, 2023)
This article presents the reality of speech expressed by the Governor of West Nusa Tenggara via his Facebook account. Data collection used documentation techniques, namely by capturing images on Bang Zul Zulkieflimansyah's Facebook account which were posted in May 2022. The research results showed that the Governor of West Nusa Tengggara used his Facebook account to express himself in the form of cultural, artistic and culinary appreciation; convey an appeal; greet the public; provide motivation; providing compensation; disaster responsse activities; health information; sports information; information about attending activities; tourist attraction information; meet the characters; joke (entertainment); educational information; responsse to farmer and rancher problems; legal events; and political events. Public officials tend to (dominantly) use Facebook as a means to express themselves as figures who are popular and have social sensitivity.Tulisan ini menyajikan tentang realitas tutur yang diekspresikan oleh Gubernur Nusa Tenggara Barat melalui akun Facebook. Pengumpulan data menggunakan teknik dokumentasi, yaitu dengan menangkap gambar pada akun Facebook Bang Zul Zulkieflimansyah yang diposting pada bulan Mei 2022. Hasil penelitian menunjukkan bahwa Gubernur Nusa Tengggara Barat menggunakan akun Facebook-nya untuk mengekspresikan dirinya berupa apresiasi kebudayaan, seni, dan kuliner; menyampaikan himbauan; menyapa masyarakat; memberikan memotivasi; pemberian santunan; kegiatan respons bencana; informasi kesehatan; informasi olah raga; informasi menghadiri kegiatan; informasi objek wisata; bertemu dengan tokoh; lelucon (hiburan); informasi pendidikan; respons masalah petani dan peternak; peristiwa hukum; dan peristiwa politik. Pejabat publik cenderung (dominan) menggunakan Facebook sebagai sarana untuk mengkspresikan dirinya sebagai sosok yang merakyat dan memiliki kepekaan sosial.